¡Run for your life! the elusion of voluntary correction as an exemption from punishment by the administration - Torres Sánchez, Tessy (2019)
This work analyses the concept of voluntary correction as an exemption from punishment in Law 27444 - Law for General Administrative Procedures, and the risks that such regulation can generate in the public administration’s labor to promote compliance, given that it prevents punishment to serve as a general deterrent for the individuals; it could only a apply to permanent infractions; it doesn’t ponder the risk or damage created by the behavior; and it doesn’t establish a limit to the possibility of correction.Specific regulation issued by some of the administration’s public agencies to counter such problems has been revised, and the legislator’s purpose when regulating voluntary correction has been examined, concluding that there is a need of complement in traditional law enforcement –which has a punitive approach– with alternative and preventive mechanisms, insuffi ciently regulated and explored.